15.2k views
0 votes
(2・3)² + 5² = ??????????????????????????????????????????????

2 Answers

5 votes

Answer:

61

Explanation:

User Instant Breakfast
by
6.0k points
3 votes

Answer:

61

Explanation:

Given the exponential expression, (2・3)² + 5²:

Start by multiplying 2 and 3 inside the parenthesis, before performing other mathematical operations.

(2・3)² + 5² = (6)² + 5²

Next, perform the exponential operations for (6)² and 5², then add their squared values together:

= 36 + 25 = 61

User Tomasz Blachowicz
by
6.1k points